2012
DOI: 10.1590/s1678-69712012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da troca da firma de auditoria no gerenciamento de resultados das companhias abertas brasileiras

Abstract: O Brasil é uma das poucas nações em que o rodízio de auditores é obrigatório para companhias abertas. Assim, o país é um cenário ideal para avaliar se a qualidade das informações contábeis é impactada pela mudança - obrigatória ou voluntária - da firma de auditoria. Nesse sentido, o objetivo geral deste estudo foi verificar os efeitos da mudança da firma de auditoria no gerenciamento de resultados das companhias abertas brasileiras. A qualidade da auditoria está relacionada com o conhecimento sobre as transaçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
2
0
6
Order By: Relevance
“…Recently, after the application of the Sarbanes Oxley Act 2002 (SOX) which imposed the rotation of auditor every five years, it was found that non GAAP earnings management practices have declined, an issue that reflects that when the auditor spends longer tenure with the client, he/ she would not allow their managing of their reported earnings practices (Davis et al, 2009). In Brazil, Azevedo & Costa (2008) in preliminary study in this topic, could not infer the precise consequences of auditor changes in earnings management.…”
Section: Independent Auditing and Rotation Of Auditing Firmsmentioning
confidence: 94%
“…Recently, after the application of the Sarbanes Oxley Act 2002 (SOX) which imposed the rotation of auditor every five years, it was found that non GAAP earnings management practices have declined, an issue that reflects that when the auditor spends longer tenure with the client, he/ she would not allow their managing of their reported earnings practices (Davis et al, 2009). In Brazil, Azevedo & Costa (2008) in preliminary study in this topic, could not infer the precise consequences of auditor changes in earnings management.…”
Section: Independent Auditing and Rotation Of Auditing Firmsmentioning
confidence: 94%
“…In same sense, Silva & Bezerra (2010) concluded that changing the auditor does not influence earnings management, using the KS model in the period from 2000 to 2008. The findings of Azevedo & Costa (2012) were similar, that rotation does not reduce earnings management.…”
Section: Auditorsmentioning
confidence: 62%
“…Assim, quanto mais tempo de relacionamento, maior a qualidade dos serviços de auditoria e maior qualidade da informação contábil reportada pelo cliente (Ghosh & Moon, 2005, Jenkins & Velury, 2008, Azevedo & Costa, 2012. Independência: por outro lado, muitos autores consideram que um maior tempo de relacionamento faz com que o auditor tenha uma maior proximidade do seu cliente, o que afeta negativamente a qualidade dos serviços prestados.…”
Section: B) Tempo De Prestação De Serviços De Auditoria No Clienteunclassified
“…Mas deve-se ressaltar que a literatura também contempla que a maior relação entre o auditor e o cliente auditado pode ser benéfica pelo fato de que esse profissional adquire ao longo do tempo maiores conhecimentos sobre o cliente e o seu ramo de atividade (De Fond & Subramanyam, 1998;Ghosh & Moon, 2005;Jenkins & Velury, 2008;Li, 2010;Azevedo & Costa, 2012). Entretanto, partindo da primeira suposição, tem-se a terceira hipótese de pesquisa:…”
Section: Hipóteses Do Trabalhounclassified